Here is a very good video by Alphonso Gracia-Saz to prove that infinity minus infinity cannot be determined.

\infty - \infty \neq \infty

The best way to solve when you get an \infty - \infty is we try to rewrite it and manipulate it algebraically as shown below

https://www.youtube.com/watch?v=3EyFtXgJXTg&ab_channel=DKdemy

I found an answer from www.quora.com

**What is infinity minus infinity**? - Quora

Mathematical equations with **infinity** are not impossible to do. However, one must
remember that **infinity** is not able to be exhausted. Because of this, there are ...

For more information, see **What is infinity minus infinity**? - Quora

I found an answer from math.stackexchange.com

calculus - What is the result of $\infty - \infty$? - Mathematics Stack ...

Aug 30, 2011 **...** Perhaps an uninteresting way of speaking about infinity, but one you surely will
understand, the first one I was ...... That's **infinity minus infinity**.

For more information, see calculus - What is the result of $\infty - \infty$? - Mathematics Stack ...

I found an answer from answers.yahoo.com

What's **infinity minus infinity**? | Yahoo Answers

At first, you may think that **infinity** subtracted from **infinity** is equal to zero. After all,
any number subtracted by itself is equal to zero, however ...

For more information, see What's **infinity minus infinity**? | Yahoo Answers

I found an answer from en.wikipedia.org

Indeterminate form - Wikipedia

In calculus and other branches of mathematical analysis, limits involving an
algebraic ... Note that zero to the power **infinity** is not an indeterminate form.

For more information, see Indeterminate form - Wikipedia

Infinity - Infinity = indeterminate

\infty - \infty = indeterminate

Example

Case 1:

= \lim_{x \to \infty} (2x -x)

= \lim_{x \to \infty} (2x) - \lim_{x \to \infty} (x)

= \infty - \infty

= + \infty

Case 2:

= \lim_{x \to \infty} (x - 2x)

= \lim_{x \to \infty} (x) - \lim_{x \to \infty} (2x)

= \infty - \infty

= - \infty

Case 3:

= \lim_{x \to \infty} (x - x)

= \infty - \infty

= 0

Hence, we can conclude that \infty - \infty = indeterminate. Because we have different responses ( + \infty,-\infty, \text{ and } 0 ) in each case, we are unable to figure out that this is the exact answer.